Effects of self selection in architectural design process (ADP) ; considering end user’s personalization (EUP) / Mahdi Torabi , Mahmud Mohd Jusan and Alireza Daneshpour - Torabi, Mahdi; Mohd Jusan, Mahmud; Daneshpour, Alireza (2012)
Diversity of human requirements in his living environment is obvious. Architecture ideal is to respond to such diverse requirements. The Architectural Design Process (ADP) which has been defined for this basic purpose aims at fulfilling not only physical and functional but also psychological human needs. Recent trends in architectural design show that in most of the cases, the focus of ADP has been shifted to the business goals, fancy features and technological capabilities. Even if none of these approaches can be blamed, what has been lost here is a mere respect to human values. In this regard, paying attention to end users’ ideas, believes, attitudes and desires, which are known as self-selection in thisresearch, can be considered as an appropriate method for deriving final users’ values. The literature review demonstrates that End User’s Personalization (EUP) is the closest concept to self-selection, in which both emphasis are on the importance of end-users’ values and ideas. In other words, it can be said that personalization is a format of self-selection on end-users’ side. Designing according to EUP principles would lead us to present more efficient, satisfying and desirable product which consequently results in increasing of our output’s appeal for final users